Evaluación del funcionamiento de puntos limpios analizando la aceptación de la comunidad en la administración zonal La Delicia fase 1 y planteamiento de guías para el aprovechamiento de material recuperado - Guevara Calero, Andrea Katherine (2013)
The present work is based on the data collection and its Massive and volumetric quantification of recyclable material in urbanizations Zonal Administration the Delight. The data collection was developed in a time of six months ranging from 6 June, until December 10, 2012. Obtaining quantities by weight of the Different segregation of recyclable material such as paper, cardboard, PET, plastic and glass. Through a field survey before performing the monitoring or taking of data was observed in the different developments that all the recyclable material together with the unusable material was deposited in the containers of common waste (Municipal Containers), which ended in the landfill thus losing its economic value and the utility that can have Many of them when being recycled. The data collection was done to determine the amount of recyclable material that was is recovering in the current and future population. With these results obtained propose guidelines for the use of recovered recyclable material. Knowing the actual amount by weight of recyclable material that is being recovered, making the determination of fractions of segregation in the study area and its percentage calculations corresponding to the different urbanizations of the AZLD. This is not only an environmental project but also a social one since it has the active participation of smaller scale Environmental Managers (SMEs), with the goal of improving the income and the quality of life of the people that in a way informal they carry out the recovery and recycling of this waste.